ANALISIS KANDUNGAN LOGAM BERAT Pb PADA SEDIMEN dan KERANG DARAH (Genus: Anadara) di PERAIRAN PANTAI LABUHAN TERENG KABUPATEN LOMBOK BARAT - Meyla Fitri Handayani; Muhlis Muhlis; Erin Ryantin Gunawan (Jurnal Penelitian Pendidikan IPA, 2016)
The aims of this research are to analyze the content of Lead in blood cockle (Genus: Anadara) at West Lombok Labuhan Tereng coastal waters. The content of lead in sediment and clams was analysis at Mataram University Analytical Laboratory by using wet digestion method and measured using atomic absorption spectrophotometer (AAS) in 283.3 nm wavelength. The results then compared with the sediments and clams standards applicable. Results of Pb in the sediment measurements show that the highest lead levels is 30.66 mg/kg found in around Dusun Cemara coast. The results obtained are still at the level targets under Dutch Quality Standards for Metals in sediments (IADC / CEDA), 1997. The highest Pb levels in blood clams is 13,075 mg/kg contained by a medium-sized (3.08 cm) of species A. antiquata around Kebon Talo estuary. These results are indicate that the levels of Pb in blood cockle is already distant exceeded the threshold of consumption under Indonesian National Standar, 2009 which is equals to 1.5 mg/kg, so the clams blood in coastal waters Labuhan Tereng should not be consumed greatly overheated because the accumulative character of Pb can be harmful for health.Keywords: Blood cockle, sediment, acumulation, lead